The RANK/RANKL axis controls vascular dynamics in the bone marrow - Takeshi Kaneko; Shinya Yari; Junichi Kikuta; Yoshiki Omatsu; Shigeto Seno; Sumire Kikuchi; Kazuma Sato; Kentaro Fujii; Takao Sudo; Tetsuo Hasegawa; Kunimaro Furuta; Qianqian Guo; et al. (Proceedings of the National Academy of Sciences, 2025)
Receptor activator of nuclear factor kappa B ligand (RANKL) is an essential cytokine that induces osteoclastic differentiation by monocyte-macrophage lineage precursors. Here, we showed that in addition to its conventional action, RANKL controls vascular permeability in the bone marrow, where it facilitates the mobilization of hematopoietic monocytic cells, including osteoclast precursors, and resultantly regulates bone metabolism. RANK, a cognate receptor for RANKL, is abundantly expressed in sinusoidal endothelial cells and controls vascular permeability by regulating the expression patterns of intercellular adhesion molecule 1 and vascular cell adhesion molecule 1. High RANKL expression was detected in perivascular C–X–C motif chemokine ligand 12-abundant reticular (CAR) stromal cells. Specific deletion of RANKL expression in CAR cells abrogated the vascular leakage, suggesting that perivascular RANKL is responsible for controlling permeability. In summary, our study revealed a role for RANK/RANKL signaling as a gatekeeper of bone marrow sinusoids in vivo.